Complex agricultural landscapes host more biodiversity than simple ones: a global meta-analysis - Dataset - Estrada-Carmona, Natalia; Sánchez Bogado, Andrea Cecilia; Remans, Roseline; Jones, Sarah K. (2022)
This dataset describes the effect sizes collected and analyzed to assess non-domesticated diversity and landscape complexity interactions in agricultural landscapes. The dataset includes four tabs: 1) Effect Sizes tab: describes the 1134 effect sizes collected from 157 articles in terms of estimated effect sizes and variabilities along with cropping system, biodiversity, landscape, and study design descriptors. 2) Article description tab: describes the 614 unique articles identified through the search string and other meta-analysis or synthesis on the topic. 3) Landscape metrics directionality tab: describes the individual landscape metrics and the categorization into landscape indicators and dimensions. 4) Metadata tab: describes the content in each one of the previous tabs. The dataset includes articles conducted worldwide and published from 1977 up to 2021. (2022-07-18)